2013
DOI: 10.1128/jb.01080-13
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Virulent Broad-Host-Range Phages of Xylella fastidiosa and Xanthomonas

Abstract: The xylem-limited bacterium Xylella fastidiosa is the causal agent of several plant diseases, most notably Pierce's disease of grape and citrus variegated chlorosis. We report the isolation and characterization of the first virulent phages for X. fastidiosa, siphophages Sano and Salvo and podophages Prado and Paz, with a host range that includes Xanthomonas spp. Phages propagated on homologous hosts had observed adsorption rate constants of ϳ4 ؋ 10 ؊12 ml cell ؊1 min ؊1 for X. fastidiosa strain Temecula 1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 78 publications
2
92
0
1
Order By: Relevance
“…15 terminal repeat at both of its ends, which was also characteristic for the phiKMV-like phages Prado and Paz (Ahern et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 2 more Smart Citations
“…15 terminal repeat at both of its ends, which was also characteristic for the phiKMV-like phages Prado and Paz (Ahern et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…A single unit DNA-dependent RNA polymerase (RNAP) gene was found at the end of the Class II gene cluster. The Xaj24 phage was most similar to the Prado phage (accession number: KF626667); (Ahern et al, 2014), as the two phages shared 67.8 % identity at nucleotide level. The Xaj24 genome contained a 482 bp direct…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…Open reading frames (ORF) were automatically identified employing Rapid Annotation using Subsystem Technology (RAST) (http://rast.nmpdr.org/) [41] and Geneious software (Biomatters Limited). Additional protein homology searches of nucleotide sequences and manual annotation of putative translated ORF products were carried out using blastx at NCBI (http://blast.ncbi.nlm.nih.gov) against a nonredundant protein sequence database (E value cut-off <10 -4 ) [3] to compare the homologies with known protein sequences. Finally, the genome annotation was mapped using Geneious software.…”
Section: Methodsmentioning
confidence: 99%
“…Phages are environmentally ubiquitous, with an estimated 10 31 particles on earth [1,2]. Metagenomic analyses have revealed that they are immensely diverse and present in almost all niches where bacterial cells are present [3,4]. Phages have the capability to kill specific bacteria during exponential bacterial growth.…”
Section: Introductionmentioning
confidence: 99%